2018
DOI: 10.1186/s13075-018-1516-0
|View full text |Cite
|
Sign up to set email alerts
|

Altered white matter microstructure in lupus patients: a diffusion tensor imaging study

Abstract: BackgroundThe purpose of this study was to investigate whether white matter microstructure is altered in patients suffering from systemic lupus erythematosus (SLE), and if so, whether such alterations differed between patients with and without neuropsychiatric symptoms.MethodsStructural MRI and diffusion tensor imaging (DTI) were performed in 64 female SLE patients (mean age 36.9 years, range 18.2–52.2 years) and 21 healthy controls (mean age 36.7 years, range 23.3–51.2 years) in conjunction with clinical exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 53 publications
(59 reference statements)
2
37
1
Order By: Relevance
“…Additional longitudinal studies are needed to verify this prediction. While several studies have reported WM alterations in NPSLE compared with HC subjects in segments of the CC, the forceps, anterior corona radiata, thalamus, and parietal and frontal lobes (33-36) and overall diminished volume of the CC (34, 37), our results support the growing body of literature demonstrating significant WM abnormalities in SLE subjects without acute neuropsychiatric manifestations (38)(39)(40)(41)(42). Most of these studies in SLE subjects without neuropsychiatric manifestations failed to demonstrate significant correlations between diminished WM integrity and cognition.…”
Section: Table 4 Brain Regions With Significant Differences In Fa Besupporting
confidence: 86%
“…Additional longitudinal studies are needed to verify this prediction. While several studies have reported WM alterations in NPSLE compared with HC subjects in segments of the CC, the forceps, anterior corona radiata, thalamus, and parietal and frontal lobes (33-36) and overall diminished volume of the CC (34, 37), our results support the growing body of literature demonstrating significant WM abnormalities in SLE subjects without acute neuropsychiatric manifestations (38)(39)(40)(41)(42). Most of these studies in SLE subjects without neuropsychiatric manifestations failed to demonstrate significant correlations between diminished WM integrity and cognition.…”
Section: Table 4 Brain Regions With Significant Differences In Fa Besupporting
confidence: 86%
“…In a previous study on diffusion tensor imaging in SLE‐patients, we concluded that the white matter microstructure in SLE patients was altered in areas crucial for attention, mood, and cognitive functions. Importantly, this was also the case in patients without NP‐involvement (Nystedt, Nilsson, et al, ).…”
Section: Introductionmentioning
confidence: 63%
“…Today, several advanced imaging modalities exist. These include diffusion-weighted imaging (DWI) [ 105 ], magnetic transfer imaging (MTI) [ 106 ], magnetic resonance angiography (MRA) [ 107 ], magnetic resonance spectroscopy (MRS) [ 108 ], diffusion tensor imaging (DTI) [ 109 ], and blood oxygen level-dependent functional MRI (BOLD-fMRI) [ 93 ], and they ideally could be implemented for identifying functional hallmarks of NPSLE and allow its diagnosis [ 11 , 110 ]. These methods are not detailed here, as this review rather focuses on data obtained in preclinical research performed on murine NPSLE models.…”
Section: Neuroimaging In Npslementioning
confidence: 99%